Natural Disasters and Food Crises in Low-Income Countries : Macroeconomic Dimensions - Adedeji, Olumuyiwa (IMF Working Papers; Working Paper ;, 2016)
The exposure of low-income countries to natural disasters has a significant impact on food production and food security. This paper provides a framework for assessing a country's vulnerability to food crisis in the event of natural disasters. The paper finds that macroeconomic and structural indicators that are crucial for ensuring the resilience of low-income countries to adverse external shocks are equally important for minimizing the occurrence of food crisis in the event of natural disasters.